Persepsi Sarjana Akuntansi Tentang Kompetensi Akuntan Profesional - Rohmah, Fajriyani Nur; Challen, Auliffi Ermian; Utie, Maulida Salmi (Journal of Accounting, Management, and Economics Research (JAMER), 2025)
Problems in employment are increasingly faced by every Bachelor graduate. Graduates who do not have competence will find it difficult to be absorbed into the workforce, therefore, to be able to compete in this era of globalization, competence in their fields is needed to prepare graduates to become a skilled and competitive workforce. An accountant is also required to be able to have competence in their field to perform accounting tasks properly so that they can maintain public trust. This study aims to analyze the accountant competencies possessed by graduates of the Accounting Study Program, Faculty of Economics and Business, YARSI University. The competency areas studied based on IAESB 2019 are intellectual skills, interpersonal and communication skills, personal skills, organizational skills. The method used in this research is qualitative with a descriptive type using a survey of respondents' perceptions. The results of this study indicate the order of the most needed is 1) personal skills, 2) interpersonal and communication skills, 3) intellectual skills, 4) organizational skills